Decentralization and Deconcentration in Morocco : Cross-Sectoral Status Review - World Bank (Washington, DC, 2014)
This report will look at how the Government of Morocco (GoM) has addressed the issues of decentralization and deconcentration in recent years. It discusses how these processes have affected public policies at the sub-national level and a number of strategic sectors, including agriculture, irrigation, water and waste water, health, education, energy, transport, urban, housing, and solid waste management. Specifically, the report will analyze the current legislative and institutional arrangements governing sub-national accountability, revenue and spending powers, and public service management at the sub-national level and within the strategic sectors. It is to serve as background input for the World Bank team preparing the new Country Partnership Strategy (CPS) 2010/2013. The Report builds on the findings from project appraisal documents, economic and sector work, policy notes, mission aide memoires, and implementation completion reports already completed by the World Bank.